Jayme’s scientific contributions in the area of Convexity in Graphs - Coelho, Erika; Dourado, Mitre; Nascimento, Julliano; dos Santos, Vinicius (Cadernos do IME - Série Informática, 2022)
We survey some of the contributions of Professor Jayme Luiz Szwarcfiter in the area of graph convexity, in celebration of his 80th birthday.